Carbohydrate oxidation from a drink during running compared with cycling exercise - Pfeiffer, B.; Stellingwerff, T.; Zaltas, E.; Hodgson, A. B.; Jeukendrup, A. E. (Medicine & Science in Sports & Exercise, 2011)
Current recommendations for CHO intake in the field for all modes of endurance exercise are largely on the basis of laboratory studies that measured oxidation of ingested CHO. However, the majority of these laboratory studies used cycling as the mode of exercise, and it is not known whether these results can be extrapolated to running.